Nonlinear societal change: The perspective of dynamical systems. (22nd August 2018) - Nowak, Andrzej; Vallacher, Robin R.
Abstract : Although rapid social change reflects each society's unique combination of myriad social, historical, political, and economic factors, we argue that the defining features of such change can be understood with recourse to the dynamic processes inherent in complex systems. Accordingly, we present a formal model that describes, in minimalist terms, the dynamics associated with rapid societal transitions in a society's norms and attitudes—and to the potential for rapid reversals of these transitions. The model predicts that societies in the midst of rapid change are characterized by dual realities corresponding to the new and the old, so that models focusing only on changes in the central tendency of a societal attitude provide a misleading account of rapid social change. This model is implemented in computer simulations and validated with empirical data concerning the transition in Eastern Europe from communism to democracy and a free market economy in the late 1980s.